Descarte de resíduos resultantes da atividade de vacinação da rede municipal de Palmas – TO: uma abordagem com foco na saúde do trabalhador e na preservação do meio ambiente - Santos, Jânia Oliveira (Universidade Federal do Tocantins, 2017)
This is a descriptive study carried out in the 31 Health Units (HU) of Unified Health System (SUS) that administer vaccines in Palmas, Tocantins - Brazil, in order to compare the professional practices of vaccination waste disposal with the federal technical regulation that refers to the health waste management, with emphasis on RCD 306/2004 of ANVISA and resolution 358/2005 of the National Environment Council, in addition to the Brazilian Association of Technical Standards (ABNT) regulations. It was also sought to identify actions taken in the HU that minimize the generation of vaccination residues and that expose the environment and workers to contamination risks. The data were collected from June to November of 2016 through direct observation using a road map composed of different phases of waste management, and then analyzed using descriptive statistics. When comparing the practices carried out with the legislation recommendations and ABNT regulations regarding health service residues, it was observed that in all health units there were flaws related to the management of vaccination residues, and intraestablishment were predominant. Such a reality can expose workers, users and the environment to contamination risk. It is necessary to review the vaccination waste management practices that are carried out in public health units in Palmas-TO, as well as to train vaccination room professionals on the subject.